Generalized phase stability in multipacting - Valery Shemelin (Physical Review Special Topics. Accelerators and Beams, 2011)
Analysis of known experimental data for the boundaries of the multipactor discharge in a flat gap shows that these data cannot be explained in the frames of a simple two-point theory. More complicated theories include repeating impacts of the electrons on the same surface before they hit the opposite one. Here an approach is proposed that can illustrate many of these theories: a phase map connecting the start and arrival phases of the electrons coming to the same or opposite plate. This illustrative technique leads to a concept of a generalized phase stability. Introduction of the generalized condition of stability helps to understand the expanding of multipacting zones beyond the limits predicted by the simple stability condition. The phase diagrams illustrate the phase motion when the simple condition of stability is applicable or not applicable.